Economic efficiency of the “Tes” horse (Mongolian Journal of Agricultural Sciences, 2021)
The “Tes” horse, developed mainly through natural selection, is strong enough to survive long and severe subzero spells. The “Tes” horses live outdoors all year at 30 °C (86 °F) in summer down to −50 °C (−40 °F) in winter, and search for food on their own. Strong, fast and hardy, the “Tes” horse is the lord of the steppe. The main stock of Tes horse breed is now kept in Tes and Zuungovi soum of Uvs province, Tes and Bayantes soum of Zavkhan province,Tsetserleg and Tsagaan-uul soum of Khuvsgul province of Mongolia. The profit margin per head of Tes horses is 67%, which is 10% higher than that of “Mongol” horses and at the same level as that of “Galshar” horses, as calculated by research team in 2019. The average live weight of “Tes” horses is 40-50 kg for stallions and 5-10 kg for mares, which is higher than “Mongol” and “Galshar” horses. It is economically viable for meat production.“Тэс” адууны эдийн засгийн ашигТэс угшлын адууны 1 толгойгоос олж байгаа ашигт ажиллагааны төвшин  67% байгаа нь Монгол үүлдрийн адууныхаас 10%-иар илүү, Галшар үүлдрийн адууныхтай ижил төвшинд байна. Байгалийн эрс тэс уур амьсгалтай газар нутагт дасан зохицох чадвар өндөр тул уналга эдэлгээ, усч, тэсвэр тэвчээрээр илүү,  өвчлөл бага байгаа нь өрхий аж ахуйн хувьд өндөр ач холбогдолтой. Үүнийг нийт судалгаанд хамрагдсан малчдын 96% нь хариулсан байна. Мөн адууны зүй бус хорогдол, гүүний хээл хаялт бага байгаа нь тухайн газар нутагт дасан зохицсон, өрхийн орлогын хувьд тогтвортой  аж ахуй болох нь харагдаж байна.